2019
DOI: 10.1136/tsaco-2018-000259
|View full text |Cite
|
Sign up to set email alerts
|

Causes and outcomes of traumatic brain injuries in Uganda: analysis from a pilot hospital registry

Abstract: BackgroundTraumatic brain injury (TBI) is an important cause of morbidity and mortality in low/middle-income countries. The objective was to assess causes and outcomes of unintentional and intentional TBI among patients presenting to a tertiary care hospital in Uganda.MethodsThis study was conducted at Mulago National Referral Hospital, Kampala, Uganda, for 15 months in 2016–2017. Patients of all ages, males and females, presenting to the emergency department with suspected or documented TBI were enrolled. Pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
18
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 29 publications
4
18
0
3
Order By: Relevance
“…Another study by Tran et al (2015) found that males aged 15–29 years comprised the predominant demographic with a male:female ratio of 4.5:1. Similarly, Zia et al (2019) studied 3,749 TBI patients, with over 70% of patients between 19–45 years age group and 80% were males. This could be linked to males being more active within occupational sectors characterized by high risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study by Tran et al (2015) found that males aged 15–29 years comprised the predominant demographic with a male:female ratio of 4.5:1. Similarly, Zia et al (2019) studied 3,749 TBI patients, with over 70% of patients between 19–45 years age group and 80% were males. This could be linked to males being more active within occupational sectors characterized by high risk.…”
Section: Discussionmentioning
confidence: 99%
“…Over 90% of TBI related deaths disproportionately occur in low- and middle-income countries such as those in the African region ( Johnson & Griswold, 2017 ). In Uganda, such deaths from TBI mainly result from fatal road traffic crashes ( Zia et al, 2019 ) and delayed presentation to health facilities ( Vaca et al, 2019 ). Described as a silent epidemic, the World Health Organization (WHO) projected that by 2020, road traffic injuries (RTI) will be a major cause of TBI and will rank 3rd as a leading cause of disability adjusted life years lost ( World Health Organization, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…In high-income countries (HICs), these strategies have been implemented in various forms which range from adapting the environment, legislation, safety education and skills training, to strengthening post-trauma response systems and improving access to acute and postacute care [14,[18][19][20][21]. However, LMICs often lag far behind in this area despite the higher toll of neurotrauma in these societies [4,6,22]. It is also clear that not all HIC approaches may be applicable to the LMIC context due to differences in environment, resources, population, culture and infrastructure [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…In high income countries (HICs), these strategies have been implemented in various forms which range from adapting the environment, legislation, safety education and skills training, to strengthening post-trauma response systems and improving access to acute and post-acute care [14,[18][19][20][21]. However, LMICs often lag far behind in this area despite the higher toll of neurotrauma in these societies [4,6,22]. It is also clear that not all HIC approaches may be applicable to the LMIC context due to differences in environment, resources, population, culture and infrastructure [23,24].…”
Section: Introductionmentioning
confidence: 99%